Fffff, paf, crach! - Woodward, Kay.; Colnaghi, Stefania (Columbus, OH : School Specialty Pub., 2005)
Kate makes a variety of noises as she plays, stepping in mud, paint, and snow, and eating her favorite foods, after which it is time for a bath.
Preschool.
Keywords: Cleanliness -- Juvenile fiction; Sound -- Juvenile fiction; Spanish language materials